Implementasi Metode Multi Objective Optimization On The Basis Of Ratio Analysis (MOORA) Untuk Penentuan Agen 46 BNI Cabang Pembantu Tulang Bawang - M. Abu Jihad Plaza R; Haliq Haliq (ISB Atma Luhur, 2021)
BNI Tulang Bawang Sub-Branch Office has provided banking services to the public, in determining, agents 46 have used a computerized process but still use Ms. Excell where not all users can operate Ms. Excell well, for that we need a calculation method and an application that can be used by all users using a model that matches the criteria set by BNI Bank, namely bank statements, business status, income, home status and survey results. One of the decision support system methods that can be used is the Multi Objective Optimization method on the basis of Ratio Analysis (MOORA) which is a multi ¬- objective system that optimizes two or more criteria in assisting decision making using the Borland Delphi 10 application so that the results are more precise and effective. The results of the calculation of the Multi Objective Optimization method On The Basis Of Ratio Analysis (MOORA) which was built with the Borland Delphi application resulted in a decision from the process of 15 samples, received 7 and rejected 8 data of Agent 46.